THE EFFECT OF PROFIT QUALITY AND PROFITABILITY ON COMPANY VALUE WITH GOOD CORPORATE GOVERNANCE AS A MODERATION VARIABLE (EMPIRICAL STUDY ON MANUFACTURING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE IN 2020-2022) - Wiliyanto Wiliyanto; MuammarAfif Al Qusaeri, M; Wahab Khasbullah; Fakhurozak Fakhurozak; Muthiatul Khasanah (Universitas Dharmawangsa Medan, 2026)
This study aims to analyze the effect of earnings quality and profitability on firm value with Good Corporate Governance (GCG) as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2022 period. Firm value is measured using Price to Book Value (PBV), earnings quality is proxied by Total Accruals (TACC), profitability is measured using Return on Assets (ROA), while GCG is proxied by managerial ownership. This research employs a quantitative associative approach using secondary data obtained from the annual financial reports of manufacturing companies published by the IDX. The sample was selected using a purposive sampling technique, resulting in 41 manufacturing companies observed over a three-year period, yielding a total of 123 observations. Data analysis was conducted using multiple linear regression and Moderated Regression Analysis (MRA). The results indicate that earnings quality has a positive and significant effect on firm value. Profitability also has a positive and significant effect on firm value. Furthermore, Good Corporate Governance is proven to moderate and strengthen the relationship between earnings quality and firm value. However, Good Corporate Governance does not moderate the relationship between profitability and firm value. These findings suggest that earnings quality and profitability are important factors in enhancing firm value, while the implementation of good corporate governance can increase investors’ confidence in the credibility of the earnings information reported by companies. Keywords: Earnings Quality, Profitability, Firm Value, Good Corporate Governance, Manufacturing Companies